Canine mesenchymal stem cells from synovium have a higher chondrogenic potential than those from infrapatellar fat pad, adipose tissue, and bone marrow. - Akari Sasaki; Mitsuru Mizuno; Nobutake Ozeki; Hisako Katano; Koji Otabe; Kunikazu Tsuji; Hideyuki Koga; Manabu Mochizuki; Ichiro Sekiya (PLoS ONE, 2018)
Osteoarthritis (OA), a common chronic joint disorder in both humans and canines, is characterized by a progressive loss of articular cartilage. Canines can serve as an animal model of OA for human medicine, and this research can simultaneously establish effective veterinary treatments for canine OA. One attractive treatment that can lead to cartilage regeneration is the use of mesenchymal stem cells (MSCs). However, for canine OA, little information is available regarding the best source of MSCs. The purpose of this study was to identify a promising MSC source for canine cartilage regeneration. We collected synovial, infrapatellar fat pad, inguinal adipose, and bone marrow tissues from six canines and then conducted a donor-matched comparison of the properties of MSCs derived from these four tissues. We examined the surface epitope expression, proliferation capacity, and trilineage differentiation potential of all four populations. Adherent cells derived from all four tissue sources exhibited positivity for CD90 and CD44 and negativity for CD45 and CD11b. The positive rate for CD90 was higher for synovium-derived than for adipose-derived and bone marrow-derived MSCs. Synovium-derived and infrapatellar fat pad-derived MSCs displayed substantial proliferation ability, and all four populations underwent trilineage differentiation. During chondrogenesis, the wet weight was heavier for cartilage pellets derived from synovium MSCs than from the other three sources. The synovium is therefore a promising source for MSCs for canine cartilage regeneration. Our findings provide useful information about canine MSCs that may be applicable to regenerative medicine for treatment of OA.